Sexuality and menopause in women over 39 years - Castañeda, Carla (2015)
OBJECTIVE: To determine the characteristics of sexuality in women over 39 years in a region of the Peruvian jungle. MATERIALS AND METHODS: Survey of 25 questions on sexuality, with multiple, anonymous and voluntary 145 women> 40 years specific alternatives. RESULTS: One hundred twenty women adequately resolved the survey. 18.3% were menopausal; 45.8% two years ago did not enjoy sex with your partner, which correlated with age> 60. Those who still liked sex were married or cohabiting and generally <50 years. Factors associated with not enjoy sex, were lack of desire and dyspareunia. 38.3% wanted their sex life was like before. There was a close relationship between lack of desire and the negative answer to this question (p <0.001). CONCLUSIONS: Women Lamas left to find sexual pleasure between 50 and 60 years. For the sexual life, the fact of menstruation was not associated with sexual pleasure. Who had adequate sexual life, they wanted to continue having a good sexuality, even more important factor than age.